Approaches to reporting incidents and adverse events in large hospitals: Integrative review (Research, Society and Development, 2022)
It is a case of an integrative review of the approaches used to report incidents and adverse events in hospitalized patients, aiming to: conduct an integrative review of incident and adverse event reporting approaches adopted in large hospitals. Integrative review study with qualitative approach, descriptive in nature. Data were collected in Latin American and Caribbean Literature in Health Sciences, PubMed databases, in the time frame from 2011 to 2021 and submitted to analysis from thematic categories. Results: Three thematic categories emerged: Tools and approaches that permeate the Notification of Incidents and Adverse Events; Contributing Factors for Underreporting of Incidents and Adverse Events in the Hospital Environment; Knowledge of Incidents and Adverse Events. It was identified that the use of a handwritten or online notification form is used on a large scale, to the detriment of the use of medical charts review; the joint work of the Patient Safety Center with the training sector is urgent and necessary; there is a need for decentralisation of reporting of adverse events and events by nursing. The factors contributing to underreporting were based on fear of blaming on the part of institutions. As to the incidence of adverse events, errors in medication administration, were highlighted, followed by pressure injury. Conclusions: It is necessary to have permanent education regarding the notification of adverse events, with implementation of patient safety protocols and processes.